Enhancement of Solar Panel Efficiency by Comparative Analysis of Cooling Systems Utilizing Water Flow, Air Flow, and No Cooling - Pido, Rifaldo; Boli, Rahmad Hidayat; Day, Randy Rianto (Mechanical Engineering Department - Institut Teknologi Adhi Tama Surabaya, 2025)
This paper presents the results of a study on increasing the efficiency of solar panels with a comparative analysis of cooling systems utilizing air flow, air and without cooling. The method with cooling flow is used to absorb heat generated by the PV module. This study was designed simply and effectively, tested in outdoor conditions. The rear surface of the PV panel was flowed with a fluid that was in direct contact. The results showed that solar panels with air cooling systems were relatively more effective compared to other cooling systems, namely being able to increase output power by 36.50 watts and efficiency by 12.7%, compared to air cooling systems with output power of 34.56 watts and efficiency of 11.12%, while for solar panels without cooling the output power was 31.01 watts and efficiency of 10.56%.